2021
DOI: 10.1038/s41588-021-00828-9
|View full text |Cite
|
Sign up to set email alerts
|

Minor intron retention drives clonal hematopoietic disorders and diverse cancer predisposition

Abstract: Most eukaryotes harbor two distinct pre-mRNA splicing machineries: the major spliceosome, which removes >99% of introns, and the minor spliceosome, which removes rare, evolutionarily conserved introns 1 – 4 . Although hypothesized to serve important regulatory functions 5 , physiologic roles for the minor spliceosome are not well understood. For example, the minor spliceosome component ZRSR2 is subject to recurrent, leukemia-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 63 publications
(94 reference statements)
1
77
0
1
Order By: Relevance
“…In this model, Zrsr2 loss leads to a global impairment of U12-type intron splicing with over one-third of U12-type introns exhibiting significantly increased retention. Interestingly, Zrsr2-null HSCs show enhanced self-renewal and MDS [183].…”
Section: Box 1 Splicing Factors Most Frequently Mutated In Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, Zrsr2 loss leads to a global impairment of U12-type intron splicing with over one-third of U12-type introns exhibiting significantly increased retention. Interestingly, Zrsr2-null HSCs show enhanced self-renewal and MDS [183].…”
Section: Box 1 Splicing Factors Most Frequently Mutated In Mdsmentioning
confidence: 99%
“…Very recently, to investigate the impact of ZRSR2 mutations on minor intron splicing, Inoue and colleagues created a mouse model through the conditional Cre-mediated excision of exon 4 of Zrsr2, resulting in an early frameshift [183]. In this model, Zrsr2 loss leads to a global impairment of U12-type intron splicing with over one-third of U12-type introns exhibiting significantly increased retention.…”
Section: Box 1 Splicing Factors Most Frequently Mutated In Mdsmentioning
confidence: 99%
“…Most recently, it was demonstrated that impaired minor intron excision by knock-out of ZRSR2 protein enhances hematopoietic stem cell self-renewal, and mutations in minor introns are suggested to be potential cancer drivers [83]. However, the precise molecular mechanism how ZRSR2 mutations affect minor intron splicing remains to be elucidated.…”
Section: Zrsr2mentioning
confidence: 99%
“…The congenital disorders related to minor intron splicing include: spondyloepiphyseal dysplasia tarda (SEDT) [ 86 ], Microcephalic Osteodysplastic Primordial Dwarfism type I/III or Taybi-Linder syndrome (MOPDI/III or TALS) [ 89 , 104 ], Roifman syndrome (RFMN) [ 91 ], Lowry Wood syndrome (LWS) [ 90 ], early-onset cerebellar ataxia (EOCA) [ 87 ], isolated growth hormone deficiency (IGHD) [ 74 ] (reviewed in [39.72]), and Noonan syndrome [ 88 ]. On the other hand, the neurodegenerative diseases include spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS) (reviewed in [ 39 , 72 ]).…”
Section: Minor Intron Splicing and Diseasesmentioning
confidence: 99%
“…However, the high similarity of the two pathways in their physiological states and the prevalence of alternative splicing in the minor splicing pathway [ 55 ] suggest that the two pathways are affected similarly in pathological states. Furthermore, the minor splicing system has been linked to myelodysplastic syndrome [ 71 , 88 ] and Peutz-Jegher’s syndrome [ 85 ], which increase the risk of acute myeloid leukemia [ 71 ] and gastrointestinal/extra gastrointestinal cancers [ 105 ], respectively. The cause of six congenital diseases and two neurodegenerative disorders have been attributed completely or in part to the minor splicing pathway.…”
Section: Minor Intron Splicing and Diseasesmentioning
confidence: 99%